THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND GREEN HUMAN RESOURCES MANAGEMENT ON COMPETITIVE ADVANTAGE MEDIATED BY SELF EFFICACY AT MIXUE OUTLETS IN CIKARANG - Cut Andriani Zulkarnain; Retno Purwani Setyaningrum (Dynamic Management Journal, 2023)
Companies today must have the ability to compete so that the company will not be eliminated by other competitors. The purpose of this study was to determine the effect of transformational leadership and green human resources management on self-efficacy with competitive advantage as a moderating variable. This study uses a quantitative method with the sample size being millennial generation employees who work at Mixue in the Cikarang area with a total of 60 respondents. This research was processed using SmartPLS 3.0 data processing software and data collection was done through Google forms. The results showed that: (1) there is a positive and significant influence of transformational leadership on competitive advantage, (2) there is no significant influence of green human resources management on competitive advantage, (3) there is a positive and significant influence of self-efficacy on competitive advantage, (4) there is a positive and significant influence of transformational leadership on competitive advantage if mediated by self-efficacy, (5) there is a positive and significant influence of green human resources management on competitive advantage if mediated by self-efficacy.